Interatomic potential and cumulants of BCC crystall under influence of anharmonic and impurity effects in exafs theory - Nguyen, Hung Van; Nguyen, Van Thi; Le, Hung Hai (VNU Journal of Science: Mathematics - Physics, 2017)
Abstracts